Assessing Nurses Problems in Pursuing Higher Education, Implementing Evidence Based Practice and Patient Care Delivery - Samina Kausar, Kalsoom Bibi, Samina Farooqi, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess problems of nurses related to higher education, evidence-based practice and patient care delivery. Study design: Cross-Sectional survey. Place and duration of study: Department of Nursing. UHS Lahore from 1st June 2019 to 31st December 2019. Methodology: Two hundred and thirteen nurses working in selected hospitals were enrolled. A self-structured questionnaire comprising of 21 questions was used for collection of data. Results: HE1, HE2, HE3 and HE4 statement had higher mean score, and the EBP1 and EBP6 statements had higher mean score. PCD6 statement had lower mean score as compared to remaining statements. Conclusion: Nurses were facing problems in pursuing higher education by not giving chance for higher education and due to unavailability of financial support. For implementing of evidence-based practices nursing professionals were not supportive and patient care delivery was affecting due to workload and inappropriate allocation of working units.